HLA–DPB1 and DPB2 are genetic loci for systemic sclerosis: A genome‐wide association study in Koreans with replication in North Americans - Zhou, Xiaodong; Lee, Jong Eun; Arnett, Frank C.; Xiong, Momiao; Park, Min Young; Yoo, Yeon Kyeong; Shin, Eun Soon; Reveille, John D.; Mayes, Maureen D.; Kim, Jin Hyun; Song, Ran; Choi, Ji Yong; et al. (Arthritis and rheumatism, 2009)
Objective To identify systemic sclerosis (SSc) susceptibility loci via a genome‐wide association study. Methods A genome‐wide association study was performed in 137 patients with SSc and 564 controls from Korea using the Affymetrix Human SNP Array 5.0. After fine‐mapping studies, the results were replicated in 1,107 SSc patients and 2,747 controls from a US Caucasian population. Results The single‐nucleotide polymorphisms (SNPs) (rs3128930, rs7763822, rs7764491, rs3117230, and rs3128965) of HLA–DPB1 and DPB2 on chromosome 6 formed a distinctive peak with log P values for association with SSc susceptibility (P = 8.16 × 10−13). Subtyping analysis of HLA–DPB1 showed that DPB1*1301 (P = 7.61 × 10−8) and DPB1*0901 (P = 2.55 × 10−5) were the subtypes most susceptible to SSc in Korean subjects. In US Caucasians, 2 pairs of SNPs, rs7763822/rs7764491 and rs3117230/rs3128965, showed strong association with SSc patients who had either circulating anti–DNA topoisomerase I (P = 7.58 × 10−17/4.84 × 10−16) or anticentromere autoantibodies (P = 1.12 × 10−3/3.2 × 10−5), respectively. Conclusion The results of our genome‐wide association study in Korean subjects indicate that the region of HLA–DPB1 and DPB2 contains the loci most susceptible to SSc in a Korean population. The confirmatory studies in US Caucasians indicate that specific SNPs of HLA–DPB1 and/or DPB2 are strongly associated with US Caucasian patients with SSc who are positive for anti–DNA topoisomerase I or anticentromere autoantibodies.